EVALUATION OF COMBUSTION BEHAVIOUR FOR INDONESIAN LOW-RANK COALS TREATED HYDROTHERMALLY - Datin Fatia Umar; Mikio Shimojo; RM. Nendaryono Madiutomo (Indonesian Mining Journal, 2018)
Hydrothermal dewatering process has been made to produce dry-processed coals, which are comparable to bituminous coal. Two types of coals, i.e. low rank and high-rank coals. The low-rank coal came from West Papua while the high one was from Central Kalimantan. The behaviour of raw and processed coals were observed using thermogravimetry and differential scanning calorimetry techniques The change in chemical properties that are based on proximate, ultimate, calorific value and Fourier-transform infrared spectroscopy analyses are studied. Those are closely related to some combustion problems. This process was conducted in a laboratory scale using an autoclave with 5,000 ml/batch in capacity at the temperature of 300 and 330°C for one hour. The results indicate that the processed coals generally have a better combustion behaviour than that of the raw coals. The processed coals have a lower reactivity than that of raw ones, due to the higher ignition temperature (Tig), char burnout temperature (Tbo) as the end of combustion and maximum combustion rate (Rmax) of processed coals. The processing temperature of the process was a slight effect on combustion behaviour. The process is very effective to improve the quality of low-rank coal, nonetheless to high-rank coal, which has low moisture content and high calorific value, and the combustion behaviour of processed coals was not significantly changed.